A STUDY OF INFLUENCING FACTORS OF CONSUMERS' WILLINGNESS TO BUY FRESH FRUITS AND VEGETABLES ONLINE IN UNDERDEVELOPED AREAS BASED ON CONSUMER SURVEY IN TONGREN CITY, GUIZHOU PROVINCE - Feng, Shitong (Journal of Buddhist Education and Research (JBER), 2022)
Consumers in underdeveloped areas in China have a huge market demand for fresh fruit and vegetable products; however, there are problems such as late popularity of online shopping, relatively low acceptance of online shopping by consumers, and unique factors affecting purchase intention. The consumers in the underdeveloped areas of China, including Guizhou province, were used as investigation objects, and the empirical research was mainly based on the five dimensions of demographic variables, the product features of preference, the acceptance of the logistics service quality, shopping platforms, degree of consumers on the influence of consumers' willingness to buy fresh fruits and vegetables online in underdeveloped areas. The empirical results showed that demographic variables had an impact on consumers' purchasing intention. Preference of product characteristics, quality of logistics service, acceptance of shopping platforms, and the degree of consumers themselves positively affected consumers' willingness to buy fresh fruits and vegetables online in underdeveloped areas. The degrees of influence from high to low included preference of product features, quality of logistics service, acceptance of shopping platform, degree of consumers. This result enables the fresh fruits and vegetables e-commerce platforms to increase the understanding of consumers' online shopping intentions in underdeveloped areas, and to fill the gaps of relevant research on consumers' online shopping intentions of fresh fruits and vegetables in underdeveloped areas.